Effects of herbal dregs supplementation of Salvia miltiorrhiza and Isatidis Radix residues improved production performance and gut microbiota abundance in late-phase laying hens - Li, Zhaonian; Ma, Ning; Gong, Xincheng; Shi, Wanyu; Meng, Xianhua; Yan, Jingjiao; Zhao, Zhiqiang; Li, Jiefeng (Frontiers in Veterinary Science, 2024)
The present study was designed to evaluate the effect of a mixture of Chinese medicinal residues (CMR) consisted of Salvia miltiorrhiza-residues (SMR) and Isatidis Radix-residues (IRR) on productive performance, egg quality, serum lipid and hormone levels, liver and blood antioxidant capacity, oviduct inflammation levels and gut microbiota in the late-laying stage. A total of 288 fifty-four-week-old BaShang Long-Tailed hens were divided into four groups. The feed trial period was 8 weeks.The control group was fed the basic diet as a CCMR group, supplemented with 3%, 4%, and 6% for experimental groups LCMR, MCMR, and HCMR. The egg production rate of the MCMR group was 8.1% higher than that of the CCMR group (P < 0.05). Serum triglyceride (TG) levels of hens of the CMR-supplemented group were significantly decreased than those of the CCMR group (P < 0.05). The group supplemented with different levels of CMR had significantly higher serum HDL-C levels compared with the control group (P < 0.05). Follicle-stimulating hormone (FSH) and Luteinizing hormone (LH) hormone levels were remarkably increased for the LCMR and MCMR groups and significantly decreased for the HCMR group compared to CCMR (P < 0.05). Serum and liver glutathione peroxidase (GSH-PX) activities were significantly rised and malondialdehyde (MDA) levels were significantly decreased in the MCMR group compared to the CCMR group (P < 0.05).The expression levels of tubal inflammatory factor markers (IL-4, IL-1β, TNF-ɑ) in the MCMR and HCMR groups were consistent with the pathological findings of the sections. As for cecal microbiota, supplementation with CMR affected the alpha